Targeting the cMET pathway to enhance immunotherapeutic approaches for mUM patients - Machiraju, Devayani; Hassel, Jessica C. (Frontiers in oncology, 2023)
The liver is the most preferential initial site of metastasis for uveal melanoma (mUM), and this preference is associated with rapid mortality in mUM patients. Despite the significant clinical benefits of Immune checkpoint inhibitors (ICIs) in metastatic cutaneous melanoma patients, ICIs have shown little to no benefit in mUM patients. A potential reason for this inefficiency of ICI could be partly devoted to the involvement of the liver itself, thanks to its rich source of growth factors and immunosuppressive microenvironment. Uveal melanoma cells show increased expression of a transmembrane protein called cMET, which is known as the sole receptor for the Hepatocyte growth factor (HGF). Hyperactivation of cMET by HGF contributes to mUM development, and the liver, being the major source of HGF, may partially explain the metastasis of uveal melanoma cells to the liver. In addition, cMET/HGF signaling has also been shown to mediate resistance to ICI treatment, directly and indirectly, involving tumor and immune cell populations. Therefore, targeting the cMET/HGF interaction may enhance the efficacy of immunotherapeutic regimes for mUM patients. Hence in this minireview, we will discuss the rationale for combining cMET inhibitors/antibodies with leading immune checkpoint inhibitors for treating mUM. We will also briefly highlight the challenges and opportunities in targeting cMET in mUM.